We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

\(\begin{align*} x + 3y + 2z &= 1,\\ -3x + y + 5z &= 10,\\ -2x - 3y +z &= 7. \end{align*}\) Solve for x, y, and z.

ant101 Dec 12, 2018

#1**+1 **

Solve the following system:

{x + 3 y + 2 z = 1 | (equation 1)

-3 x + y + 5 z = 10 | (equation 2)

-2 x - 3 y + z = 7 | (equation 3)

Swap equation 1 with equation 2:

{-(3 x) + y + 5 z = 10 | (equation 1)

x + 3 y + 2 z = 1 | (equation 2)

-(2 x) - 3 y + z = 7 | (equation 3)

Add 1/3 × (equation 1) to equation 2:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x+(10 y)/3 + (11 z)/3 = 13/3 | (equation 2)

-(2 x) - 3 y + z = 7 | (equation 3)

Multiply equation 2 by 3:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x+10 y + 11 z = 13 | (equation 2)

-(2 x) - 3 y + z = 7 | (equation 3)

Subtract 2/3 × (equation 1) from equation 3:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x+10 y + 11 z = 13 | (equation 2)

0 x - (11 y)/3 - (7 z)/3 = 1/3 | (equation 3)

Multiply equation 3 by 3:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x+10 y + 11 z = 13 | (equation 2)

0 x - 11 y - 7 z = 1 | (equation 3)

Swap equation 2 with equation 3:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x - 11 y - 7 z = 1 | (equation 2)

0 x+10 y + 11 z = 13 | (equation 3)

Add 10/11 × (equation 2) to equation 3:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x - 11 y - 7 z = 1 | (equation 2)

0 x+0 y+(51 z)/11 = 153/11 | (equation 3)

Multiply equation 3 by 11/51:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x - 11 y - 7 z = 1 | (equation 2)

0 x+0 y+z = 3 | (equation 3)

Add 7 × (equation 3) to equation 2:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x - 11 y+0 z = 22 | (equation 2)

0 x+0 y+z = 3 | (equation 3)

Divide equation 2 by -11:

{-(3 x) + y + 5 z = 10 | (equation 1)

0 x+y+0 z = -2 | (equation 2)

0 x+0 y+z = 3 | (equation 3)

Subtract equation 2 from equation 1:

{-(3 x) + 0 y+5 z = 12 | (equation 1)

0 x+y+0 z = -2 | (equation 2)

0 x+0 y+z = 3 | (equation 3)

Subtract 5 × (equation 3) from equation 1:

{-(3 x)+0 y+0 z = -3 | (equation 1)

0 x+y+0 z = -2 | (equation 2)

0 x+0 y+z = 3 | (equation 3)

Divide equation 1 by -3:

{x+0 y+0 z = 1 | (equation 1)

0 x+y+0 z = -2 | (equation 2)

0 x+0 y+z = 3 | (equation 3)

**x = 1 y = -2 z = 3**

Guest Dec 12, 2018

#3**0 **

Wow, guest. That is a lot of work. I think there is a more "compact" solution. (see below)

PartialMathematician
Dec 13, 2018

#2**+3 **

Add eq 1 and 3

-x + 3z = 8 (4)

Multiply eq 2 by 3 and add it to eq 3

-11x +16z=37

Multiply (4) by -11 and add to (5)

-17z= -58 so z=3 Sub into (4) to find x = 1

Sub these into any of the equations to find y

x+3y +2z =1

1 +3y +2(3) = 1 thus y = -2

ElectricPavlov Dec 13, 2018